Influence of Pulping Conditions on the Properties of Anatolian Black Pine (Pinus NigraArnold SSP.Pallassiana) Kraft Pulps - Ateş, S.; Kirci, H. (Informa UK Limited, 2007)
ABSTRACTAnatolian Black Pine wood chips were pulped using kraft method in laboratory scale batch digester. A series of experimental kraft pulping was carried out according to Central Composite Design (CCD) to investigate the pulping process and to study the effect of its variables (active alkali rate, sulphidity rate and Vroom's H-factor combining temperature and time) on pulp quality and yield. Second order polynomial regression equations using three independent process variables, were found to be approprite for describing kraft pulping of Anatolian Black Pine wood fibers. The derived equations were able to predict the kappa number, viscosity, yield, holocellulose and α-cellulose content of the pulp with adjusted R2 values of 96.1%, 96.8%, 86.3%, 62.5%, 96.1% and 92.2% respectively. H-factor level and the active alkali charge are the most strongly influcing all the dependent variables. In order to obtain acceptable levels of the pulp properties, high sulphidity rate (45%), medium H-factor (1600) and medi...